EFIKASI DIRI GURU BIMBINGAN DAN KONSELING TERHADAP KOMPETENSINYA - Syaiful Bahri; Nurbaity; Mutiara Sari Tobing (PENCERAHAN, 2019)
Self-efficacy is an aspect of knowledge about oneself or an attitude of feeling confident about one's own abilities in carrying out a task, which can develop self-awareness, positive thinking and to achieve goals including in facing all obstacles. This study aims to seek the self-efficacy of Guidance and Counseling teachers on their competencies. Subjects in this study were 105 Guidance and Counseling teachers in Aceh who were willing to respond and fill out questionnaires. 75.2% of the respondens had counseling and 25% had non-counseling educational background; 25% are male and 75.2% are female. The data collected through questionnaires with a scale of 11 for level dimension and a scale of 5 for of strength and generality dimension. Data analysis techniques used descriptive statistics. The results showed that guidance and counseling teachers in Aceh have predominantly considered the difficulty level of guidance and counseling competencies in easy category. Respondents are also dominantly convinced that they are capable of implementing guidance and counseling competence. Among the four sub-competencies, professional competence in general considered more difficult, weaker and smaller coverage of self-efficacy compared with other competencies such as pedagogic competence, personal and social.